In honour of Professor Ihor Yukhnovskii on the occasion of his 75th birthday (Condensed Matter Physics, 2000)
The present and the preceding issues of “Condensed Matter Physics” contain
papers written in honour of Professor Ihor Yukhnovskii on the occasion of his 75th
birthday. Professor Ihor Yukhnovskii is a well-known Ukrainian physicist, statesman
and public figure. He is a founder of the Lviv school of statistical physics. Its main
directions are the theory of liquids and electrolyte solutions, the theory of quantum
systems of interacting particles, the theory of phase transitions and critical phenomena,
theory of disordered systems and the theory of nonequilibrium processes.